2010
DOI: 10.1021/ma101019g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Self-Assembly of Amphiphilic Chiral Poly(amino acid) Star Polymers

Abstract: Reversible addition-fragmentation chain transfer (RAFT) polymerization techniques were utilized to polymerize N-acryloyl-L-phenylalanine methyl ester (L-Phe-OMe) and tetrahydropyranyl acrylate to afford amphiphilic star polymers (with 4 and 6 arms). These copolymer stars have a chiral hydrophobic core domain and can undergo further solution self-assembly to form well-defined nanostructures, which have been characterized using DLS, TEM, and cryo-TEM analysis. The characterization and properties of these novel c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 57 publications
0
44
0
1
Order By: Relevance
“…15. [203,587] 357 [357] 358 [582] 356 [239] 353 [222] 352 [222] 354 [236] 355 [427] 359 [170] 360 [533] 368 [292] 366 [486] 367 [423] 369 [58] 370 [383] 371 [245,246] 372 [464] AMPS Ϫ ϩ ϩ Ϫ ϩ ϩ Ϫ 363 [245,246] 361 [328] 362 [328] 364 [289] 365 [383] Ϫ Fig. 8.…”
Section: Monomers With Reactive Functionalitymentioning
confidence: 99%
“…15. [203,587] 357 [357] 358 [582] 356 [239] 353 [222] 352 [222] 354 [236] 355 [427] 359 [170] 360 [533] 368 [292] 366 [486] 367 [423] 369 [58] 370 [383] 371 [245,246] 372 [464] AMPS Ϫ ϩ ϩ Ϫ ϩ ϩ Ϫ 363 [245,246] 361 [328] 362 [328] 364 [289] 365 [383] Ϫ Fig. 8.…”
Section: Monomers With Reactive Functionalitymentioning
confidence: 99%
“…We have recently reported that the phenylalanine methyl ester amino acid polymer can be utilized as a substrate for chiral enhancement due to the increased interaction between opposite enantiomers. (34) In this work we wanted to explore this interaction further using our new water soluble phenylalanine polymer (PAP). We proposed that at low pH when the PAP block is hydrophobic, there should be a stronger interaction with the opposite enantiomer compared to at high pH when the polymer is hydrophilic.…”
Section: Scheme 1 Synthesis Of Amphiphilic Diblock 2 Using Raft Polymmentioning
confidence: 99%
“…54,55 Amphiphilic star block copolymers containing phenylalanine methyl esters were synthesized and their potential use in enantiomer separation was investigated. 56 Block copolymers comprising poly(acrylic acid) and poly(N-acryloyl-(L)-phenylalanine), as well as the L-and D-leucine analogs, were used to prepare shell cross-linked micelles. 57,58 Finally, the same team developed several strategies to prepare polymeric nanoreactors based on a L-proline-based monomer; such nanoreactors were shown to efficiently catalyze aldol reactions.…”
Section: Introductionmentioning
confidence: 99%